1987
DOI: 10.1007/bf01788898
|View full text |Cite
|
Sign up to set email alerts
|

Transcapillary escape rate and relative metabolic clearance of glycated and non-glycated albumin in Type 1 (insulin-dependent) diabetes mellitus

Abstract: The transcapillary escape rate and relative plasma disappearance of glycated and non-glycated albumin were measured in 25 male Type 1 (insulin-dependent) diabetic patients using a double tracer technique. The patients were divided into three groups on the basis of their urinary albumin excretion: group 1, normal albumin excretion (less than 30 mg/24 h) (n = 8); group 2, microalbuminuria (30-300 mg/24 h) (n = 9); and group 3, clinical nephropathy (greater than 300 mg/24 h) (n = 8). Six male age-matched non-diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The turnover of intra-and extravascular albumin (transcapillary exchange) is unknown in infants and children. In adults it is estimated to be ϳ5%/h (6). This equilibration between the intra-and extravascular albumin pool may have caused us to label the extravascular albumin partially as well.…”
Section: Discussionmentioning
confidence: 97%
“…The turnover of intra-and extravascular albumin (transcapillary exchange) is unknown in infants and children. In adults it is estimated to be ϳ5%/h (6). This equilibration between the intra-and extravascular albumin pool may have caused us to label the extravascular albumin partially as well.…”
Section: Discussionmentioning
confidence: 97%
“…The technique used for assessing vascular permeability, the TER of radiolabeled albumin, provides a noninvasive way of estimating rates of albumin equilibration across the vascular membrane. Other investigators have demonstrated in the basal state an increased TER of radiolabeled albumin in diabetic patients compared with nondiabetic subjects, but the cause for this vascular abnormality remains unknown (2,5).…”
Section: Discussionmentioning
confidence: 97%
“…An increased transcapillary escape rate (TER) of albumin has been demonstrated in type I diabetic patients who have microalbuminuria or clinical nephropathy (2). In these studies, the magnitude of the permeability defect seems to be related to the severity of clinical microangiopathy, particularly nephropathy (1,2,4,5).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…ACE inhibitors/ angiotensin receptor blockers and lipid-lowering agents may similarly affect plasma protein AGE levels through effects on glomerular tightening and TER, respectively (13,14). These effects on plasma protein FL and AGEs have hitherto been given little consideration, except for two previous studies (13,15). In future work, awareness of these factors would likely improve risk predictor analysis.…”
mentioning
confidence: 99%